Copper Is Accumulated as Copper Sulfide Particles, and Not Bound to Glutathione, Phytochelatins or Metallothioneins, in the Marine Alga Ulva Compressa (Chlorophyta) - Moenne-Munoz, A; Segura-Segura, R; Segura-Segura, R; Gonzalez-Figueroa, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
To analyze the mechanism of copper accumulation in the marine alga Ulva compressa, it was cultivated with 10 μM of copper, with 10 μM of copper and increasing concentrations of a sulfide donor (NaHS) for 0 to 7 days, and with 10 μM of copper and a concentration of the sulfide acceptor (hypotaurine) for 5 days. The level of intracellular copper was determined as well as the level of glutathione (GSH) and phytochelatins (PCs) and the expression of metallothioneins (UcMTs). The level of intracellular copper in the algae treated with copper increased at day 1, slightly increased until day 5 and remained unchanged until day 7. The level of copper in the algae cultivated with copper and 100 or 200 μM of NaHS continuously increased until day 7 and the copper level was higher in the algae cultivated with 200 μM of NaHS compared to 100 μM of NaHS. In contrast, the level of intracellular copper decreased in the algae treated with copper and hypotaurine. The level of intracellular copper did not correlate with the level of GSH or with the expression of UcMTs, and PCs were not detected in response to copper, or copper and NaHS. Algae treated with copper and with copper and 200 μM of NaHS for 5 days were visualized by TEM and the elemental composition of electrondense particles was analyzed by EDXS. The algae treated with copper showed electrondense particles containing copper and sulfur, but not nitrogen, and they were mainly located in the chloroplast, but also in the cytoplasm. The algae treated with copper and NaHS showed a higher level of electrondense particles containing copper and sulfur, but not nitrogen, and they were located in the chloroplast, and in the cytoplasm. Thus, copper is accumulated as copper sulfide insoluble particles, and not bound to GSH, PCs or UcMTs, in the marine alga U. compressa. © 2024 by the authors.